2016
DOI: 10.3168/jds.2015-9747
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of individual milk proteins including free amino acids in bovine milk using mid-infrared spectroscopy and their correlations with milk processing characteristics

Abstract: The aim of this study was to evaluate the effectiveness of mid-infrared spectroscopy in predicting milk protein and free amino acid (FAA) composition in bovine milk. Milk samples were collected from 7 Irish research herds and represented cows from a range of breeds, parities, and stages of lactation. Mid-infrared spectral data in the range of 900 to 5,000 cm(-1) were available for 730 milk samples; gold standard methods were used to quantify individual protein fractions and FAA of these samples with a view to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 41 publications
3
68
1
1
Order By: Relevance
“…No significant difference in recovery rate between the two quality control amino acids was identified between samples, and we observed minimal system error during detection, suggesting that the results were reliable. A previous study developed and validated the use of HPLC as a rapid method for the measurement of amino acids in milk, and a recent study reported the efficacy of mid‐infrared spectroscopy for predicting individual milk proteins, including free amino acids, in bovine milk at the population level . Another study used ultra‐performance liquid chromatography MS/MS to determine free amino acid concentrations in breast milk, but was only able to identify nine essential amino acids and 11 nonessential amino acids .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant difference in recovery rate between the two quality control amino acids was identified between samples, and we observed minimal system error during detection, suggesting that the results were reliable. A previous study developed and validated the use of HPLC as a rapid method for the measurement of amino acids in milk, and a recent study reported the efficacy of mid‐infrared spectroscopy for predicting individual milk proteins, including free amino acids, in bovine milk at the population level . Another study used ultra‐performance liquid chromatography MS/MS to determine free amino acid concentrations in breast milk, but was only able to identify nine essential amino acids and 11 nonessential amino acids .…”
Section: Resultsmentioning
confidence: 99%
“…A previous study developed and validated the use of HPLC as a rapid method for the measurement of amino acids in milk, 24 and a recent study reported the efficacy of mid-infrared spectroscopy for predicting individual milk proteins, including free amino acids, in bovine milk at the population level. 25 Another study used ultra-performance liquid chromatography MS/MS to determine free amino acid concentrations in breast milk, but was only able to identify nine essential amino acids and 11 nonessential amino acids. 26 In addition, precolumn derivatization using diethyl ethoxymethylenemalonate and HPLC was performed to determine 18 amino acids in mare's milk, 27,28 and reversed-phase HPLC was used to determine 20 free amino acids in pasteurized goat-milk cheeses.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, both milk minerals and MCP were normally distributed, and thus no data transformation was needed. Reference outliers were defined as samples whose values deviated more than 3 SD from the mean of each trait (McDermott et al, 2016a). Based on this definition, none observations for a 30 and K, 1 observation for RCT, k 20 , and Mg, 2 observations for Na and P, and 3 observations for Ca were discarded before the development of prediction models.…”
Section: Chemometric Analysismentioning
confidence: 99%
“…De Marchi et al (2014) comprehensively reviewed the use of Fourier-transform mid-infrared (FTIR) spectroscopy and many potential applications for the use of the resulting spectra as a phenotyping tool. Ongoing research includes studies of individual milk proteins and fatty acids (Lopez-Villalobos et al, 2014;McDermott et al, 2016;Bonfatti et al, 2017b) and technological properties (Cecchinato et al, 2015;Toffanin et al, 2015;Visentin et al, 2015). Studies have predicted indirect traits related to pregnancy (Lainé et al, 2017;Toledo-Alvarado et al, 2018a,b), energy status Grelet et al, 2016;Mehtiö et al, 2018), efficiency Shetty et al, 2017), and methane emissions (Vanlierde et al, 2013(Vanlierde et al, , 2015Bittante and Cipolat-Gotet, 2018).…”
Section: Introductionmentioning
confidence: 99%